Pengaruh Media Puzzle Suku Kata terhadap Keterampilan Membaca Permulaan Siswa Kelas I SDN 24 Ampenan - Lilis Setiyani; Darmiany; Muhammad Sobri (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to determine the influence of syllable Puzzle media on the beginning reading skills of first-grade students at SDN 24 Ampenan. This research is important to conduct because the initial reading skills of students are still low, as indicated by the fact that most students are not yet fluent in recognizing letters, reading syllables, and forming simple words. The research method used is a quantitative approach with a quasi-experimental type using a nonequivalent control group design. The data collection technique used was testing, while data analysis was conducted thru prerequisite tests and hypothesis tests (t-test). The research results showed that there was an improvement in initial reading skills in the experimental class with an average score increase from 48 to 78.46, while the control class only increased from 52.88 to 62.85. The hypothesis test results indicated a significant effect of using syllable Puzzle media on students' initial reading skills. The conclusion of this study is that syllable Puzzle media has a positive and significant effect on improving the beginning reading skills of first-grade students at SDN 24 Ampenan, making it a viable alternative for effective and enjoyable learning media.